Effect of cardiac rehabilitation program on patients undergoing heart transplantation - Costa, Iasmim Borges da (2024)
Introduction: Heart transplantation is a crucial option for patients with refractory heart failure, as it improves both quality of life and functional capacity. Adherence to a cardiac rehabilitation program is extremely important in the postoperative period. The objective of this literature review is to analyze the impact of cardiac rehabilitation programs on patients who have undergone heart transplantation. Methods: This is a literature review based on a search for scientific articles published between 2019 and 2024, using the databases United States National Library of Medicine (PubMed), Scientific Library Online (SciELO), and Virtual Health Library (VHL). The search utilized both English and Portuguese descriptors, resulting in 46 articles related to the topic. However, only 11 met the inclusion criteria. Results: Cardiac rehabilitation, especially when following a program that includes resistance and aerobic exercises, contributes to better prognoses in post-heart transplant patients. These programs can improve peak VO2, skeletal muscle strength, endothelial function, pulmonary capacity, and overall quality of life. Furthermore, they reduce complications such as stroke and decrease hospitalization time. Conclusion: Heart transplant patients benefit significantly when enrolled in a cardiac rehabilitation program. However, further studies are recommended to compare the effects of high-intensity interval training versus moderate-intensity continuous training in the postoperative period for heart transplant patients.